INEQUALITY DYNAMICS IN URBAN LANDUSE CHANGE IN IMPHAL OF MANIPUR (International Journal of Food and Nutritional Sciences, 2023)
Due to migration and population increase, cities are getting smaller and urban areas are growing. India's cities have seen a sharp increase in population. Today, there has been a physical shift in land usage, particularly in emerging nations, which has resulted in the loss of valuable land, with agricultural land bearing the brunt of this. The primary cause of land use change was population growth. The study's main objectives were to track changes in urban land use over a 45-year span (1970–2015) and evaluate how they affected agriculture in Imphal and the adjacent areas. During the research period, the city's build-up area grew from 22.07 sq. km to 74.16 sq. km, while the agricultural area decreased from 54.18 sq. km to 14.26 sq. km. Excessive population growth will lead to uncontrolled physical extension in all directions toward the periphery if effective planning and management are not implemented. With the aid of GIS imagery, the study, which is based on secondary data, aims to identify the process of landuse/landcover change throughout various time periods.